A note on surfaces with prescribed oriented Euclidean Gauss map - Ricardo Sa Earp; Eric Toubiana (International Journal of Mathematics and Mathematical Sciences)
We present another proof of a theorem due to Hoffman and Osserman in Euclidean space concerning the determination of a conformal immersion by its Gauss map. Our approach depends on geometric quantities, that is, the hyperbolic Gauss map G and formulae obtained in hyperbolic space. We use the idea that the Euclidean Gauss map and the hyperbolic Gauss map with some compatibility relation determine a conformal immersion, proved in a previous paper.